2019
DOI: 10.18203/2319-2003.ijbcp20191565
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral-induced adverse drug reactions in HIV-infected patients in Mali: a resource-limited setting experience

Abstract: Background: There are few reports in the literature from sub-Saharan Africa (SSA) regarding antiretroviral-induced adverse drug reactions (ADRs). Antiretroviral therapy (ART) is now widely available in SSA, and ADRs during HIV infection are also frequent. In this study, we reported the frequency and risk factors of ART-induced ADRs in a Malian population. Methods: This prospective cohort study was performed in the HIV Care and Counseling Centre (CESAC) of Mali from 2011 to 2012. Adult patients infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Adverse drug reactions (ADRs) are a major public health problem that causes increased mortality, morbidity and costs, including increased hospital admissions and length of stay [1][2][3][4][5][6][7][8][9]. Physicians, pharmacists, dentists and nurses are in a position to play a key role in pharmacovigilance programmes; however, under-reporting of ADRs is common across countries especially in low-and middle-income countries (LMICs) [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse drug reactions (ADRs) are a major public health problem that causes increased mortality, morbidity and costs, including increased hospital admissions and length of stay [1][2][3][4][5][6][7][8][9]. Physicians, pharmacists, dentists and nurses are in a position to play a key role in pharmacovigilance programmes; however, under-reporting of ADRs is common across countries especially in low-and middle-income countries (LMICs) [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 38 studies [ 45 50 , 52 , 54 64 , 66 74 , 76 , 78 , 79 , 82 84 , 89 , 90 , 92 94 ] reported the occurrence of ADEs in the outpatient setting, and four studies [ 53 , 75 , 77 , 81 ] reported ADEs in the community setting. Majority of included studies [ 18 22 , 27 29 , 32 34 , 36 , 37 , 40 , 41 , 43 , 45 – 48 , 52 , 54 60 , 62 65 , 67 , 70 , 72 – 74 , 76 , 79 , 81 , 82 , 89 , 90 , 92 94 ] were carried out on adult population (aged ≥ 18 years) ( n = 46), while 18 studies were conducted among all age groups (aged 0–100 years) [ 23 , 24 , 30 , 50 , 51 , 61 , 66 , 68 , 69 , 71 , 75 , 77 , 78 , 84 88 ], 12 studies [ 25 ...…”
Section: Resultsmentioning
confidence: 99%
“…The EFV/AZT/3TC scheme was associated with an increased risk of cardiovascular events OR1 6; 95% CI: 1.25-2.04 (54). 19 The EFV/AZT/3TC scheme was associated with an increased risk of cardiovascular events OR1 6; 95% CI: 1.25-2.0419. 19 Our series coincides in aspects such as the use of antiretrovirals such as AZT and 3TC, which could explain the frequency of arrhythmias, facts such as knowledge of this phenomenon implies making therapeutic readjustments for a better comprehensive therapeutic approach.…”
Section: Discussionmentioning
confidence: 97%
“…19 The EFV/AZT/3TC scheme was associated with an increased risk of cardiovascular events OR1 6; 95% CI: 1.25-2.0419. 19 Our series coincides in aspects such as the use of antiretrovirals such as AZT and 3TC, which could explain the frequency of arrhythmias, facts such as knowledge of this phenomenon implies making therapeutic readjustments for a better comprehensive therapeutic approach. However, Hunt et al 20 in a review of the literature published in MEDLINE and EMBASE up to August 2011, conclude that the use of protease inhibitors (PI) does not seem to be an independent predictor of QT interval prolongation as dangerous arrhythmias.…”
Section: Discussionmentioning
confidence: 97%